Impact of doctor-patient communication in health status of the indigenous people in Peninsular Malaysia - Yew, Wong Chin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The health status of the indigenous people of Peninsular Malaysia is generally considered poorer as compared to the mainstream population. Studies show that the poor health is due to various factors. One of the significant factors is poor communication between the attending doctor and indigenous patient. The objective of this study was to investigate the effectiveness of doctor-patient communications in helping to improve the health status of the indigenous communities. In-depth interviews were conducted with 18 people of the Jakun sub-ethnic of the Pahang State indigenous community. Data were transcribed, coded and subjected to thematic analysis. Results of the study show both positive and negative experiences of doctor-patient communications. Positive experiences indicated effective doctor-patient communications and thus show an increased level of confidence and trust in the attending doctor. This subsequently increases the frequency of health care visits among the indigenous communities. Whereas, negative experiences implied conflict between doctor and patient that was due to limited understanding of the language used by the attending doctor. This further causes patient being treated with minimal knowledge of their illness and patient may never return to the health care anymore. The analysis of the findings suggests that it is of utmost importance to ensure doctors understand the culture of the indigenous communities to promote effective doctor-patient communication.